Nanostructured Screen-Printed Electrodes Modified with Self-Assembled Monolayers for Determination of Metronidazole in Different Matrices - Huayhuas Chipana, B. (2014)
This paper describes the development of a sensor for the determination of metronidazole using a simple method involving the creation of nanoporous structures on gold electrodes followed by modification with self-assembled monolayers (SAMs) of thiols. The initial formation of oxidized gold species at pH 7.0 was followed by potentiodynamic reduction in order to obtain a nanostructured surface that was then modified with a SAM of cysteine. The sensor was characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), and electrochemical techniques. Quantification of metronidazole was performed using optimized square wave voltammetry. Under the best analytical conditions, the sensor operated at -0.36 V showed a linear range of 50-300 µmol L-1 and a limit of detection (LOD) of 2.6 µmol L-1. Evaluation of selectivity demonstrated that the electrode provided higher sensitivity towards nitroimidazoles. The sensor responses showed that it could be used for detection of metronidazole in different types of matrix.